Kepala Sekolah dan Guru Sebagai Garda Depan Dalam Supervisi Studi Kasus di PAUD Jambu Mede - Azizah, Wardah Azizah; Sudin, Mahmudin (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2025)
This research is designed to provide an in-depth and comprehensive description of educational supervision, with a primary focus on efforts to build the quality of educational institutions in a sustainable manner. The methodological approach applied is qualitative, through literature research involving the collection of diverse data and relevant literature needed to support the process of in-depth analysis and interpretation. Through this method, researchers strive to extract in-depth information from various trusted and credible sources. The results of this study highlight several different models of educational supervision, including conventional supervision which tends to emphasize finding errors rather than efforts to improve teacher potential, clinical supervision which is more oriented towards supporting the professional development of teachers in teaching activities, scientific supervision which emphasizes the use of questionnaires as an evaluation tool, and artistic supervision which emphasizes the importance of building a solid relationship between supervisor and teacher. In this context, the principal plays a very important role in carrying out supervision, creating a conducive school climate, providing constructive input, providing positive encouragement to education staff, and organizing acceleration programs for students who have above-average potential. Educational supervision also plays an important role in improving the quality of education through various inputs, such as an effective school organizational structure, relevant laws and regulations, clear job descriptions, as well as structured plans and procedures. Therefore, the high and low quality of input can be measured from the level of readiness of the input in supporting the overall educational process.